Examining influential factor of financial fraud on social media from the perspective of university students - Wee, Bryan Xin Jie (2024)
Financial fraud on social media has emerged as a significant concern, particularly among university students who are active users of these platforms. This study aims to investigate the influential factors affecting students' awareness of and susceptibility to financial fraud on social media. The research focuses on three key independent variables: opportunity, capability, and financial literacy.